SHOULD I LOOK OR SHOULD I BOOK - Štilić, Anđelka; Nicić, Miloš (Turističko poslovanje, 2021)
The online booking behavior of tourist website visitors shows that there is a transition from browsing to the purchasing process. Potential travelers are expected to benefit from a broad range of market opportunities made available by the Internet, with the most revolutionary of which is the probability of price reductions as a direct result of the elimination of intermediaries in the travel industry distribution chain.Customers must deal with a variety of challenges and limits when provided with various alternatives for even simple and low-cost travel bookings, and word-of-mouth from online reviews acts as a vital information source for customers.A significant component in influencing customer decision-making is eWOM and it is also a key factor in the individual booking of services and products.Customers' perception of the credibility of reviews significantly influences their behavioral intentions and the role of eWOM, in providing travel information and tourists' behavioral intent can produce “myths” on the possibility of travel savings and air tickets cost.
Keywords: turizam; avio karte; eWom; smanjenje troškova rezervacije; mitovi